INFLUENCE OF EDUCATIONAL ENVIRONMENT ON FORMATION OF REGIONAL TAX POTENTIAL - Матвеев Владимир Владимирович (Государственное и муниципальное управление, 2019)
One of the main conditions for the effective functioning of the regional economy is the availability of its own tax base. Under the current conditions, the lack of financial resources at the regional level is primarily determined by the instability of the sources of formation of the regional tax potential. The implementation of national projects in the field of education will contribute to the growth of the regional tax potential due to both the creation of new jobs,growth in wages, and in the future by increasing the intellectual potential of the region’s population, which will result in the introduction of innovations in the regional economy, contributing to the development of the real sector of the economy based on the formation of a new system of knowledge and technology.